STUDY ON THE EFFECTS OF EXPERIMENTAL DIABETES ON FERTILITY AND EARLY POSTNATAL DEVELOPMENT IN OFFSPRING OF FEMALE RATS - Azizova F.Kh., Ubaydullayeva M.A., Mahmudova Sh.I., Khuzhamuratova D.Kh., Shigakova L.A., Sobirova D.R., (Central Asian Journal of Medicine, 2025)
This research investigated the effects of experimentally induced diabetes in white outbred female rats on their fertility and the early postnatal development of their offspring. The experiment revealed that diabetes negatively impacts fertility, pregnancy progression, and physical development in newborns. In female rats with experimentally induced diabetes, pregnancy rates decreased to 62%, and the duration of pregnancy increased to 24–26 days. Offspring of diabetic females showed signs of compromised development, characterized by obesity, abnormally large size (macrosomia), and delayed milestones in physiological maturation, including later detachment of ear pinnae, slower fur growth, delayed emergence of incisors, and later opening of the eyes. These results confirm that diabetes in the maternal organism leads to decreased fertility and the birth of physiologically immature and less viable animals, highlighting the importance of monitoring the mother's health during pregnancy.